Les Grecs d’Istanbul après la conquête ottomane. - Stéphane Yerasimos (Revue des Mondes Musulmans et de la Méditerranée)
Tradition and sometimes even recent historiography allow themselves the illusion of quasi-uninterrupted continuity in the Greek-Orthodox community in the Ottoman capital following the conquest through the beginning of the 20th century. Available sources, however, seem to indicate another reality. The repopulation of the city after 1453 is undertaken practically from scratch, within a policy framework intended to encourage religious tolerance. Among the non-Muslims of the city, the Greek-Orthodox community remains predominant, as it was in the census of 1478 marking the end of repopulation. This population drops considerably however, both as a percentage and in absolute figures during the first half of the 16th century. Thus, the century which follows the conquest appears atypical in terms of the subsequent development of the Greek-Orthodox community and the backwards extrapolation and projections made from 17th and 18th century figures is not consistent with reality whether in terms of demographic impact or economic importance of this community.